Bridging the gap between microclimate and microrefugia: A bottom‐up approach reveals strong climatic and biological offsets. Issue 4 (24th November 2022) - Finocchiaro, Marie; Médail, Frédéric; Saatkamp, Arne; Diadema, Katia; Pavon, Daniel; Meineri, Eric
Abstract: In the context of global warming, a clear understanding of microrefugia—microsites enabling the survival of species populations outside their main range limits—is crucial. Several studies have identified forcing factors that are thought to favor the existence of microrefugia. However, there is a lack of evidence to conclude whether, and to what extent, the climate encountered within existing microrefugia differs from the surrounding climate. To investigate this, we adopt a "bottom‐up" approach, linking marginal disconnected populations to microclimate. We used the southernmost disconnected and abyssal populations of the circumboreal herbaceous plant Oxalis acetosella in Southern France to study whether populations in sites matching the definition of "microrefugia" occur in particularly favorable climatic conditions compared to neighboring control plots located at distances of between 50 to 100 m. Temperatures were recorded in putative microrefugia and in neighboring plots for approximately 2 years to quantify their thermal offsets. Vascular plant inventories were carried out to test whether plant communities also reflect microclimatic offsets. We found that current microclimatic dynamics are genuinely at stake in microrefugia. Microrefugia climates are systematically colder compared to those found in neighboring control plots. This pattern was more noticeable during the summer months. Abyssal populations showed stronger offsets compared to neighboring plots than the putative microrefugia occurring at higher altitudes. Plant communities demonstrate this strong spatial climatic variability, even at such a microscale approach, as species compositions systematically differed between the two plots, with species more adapted to colder and moister conditions in microrefugia compared to the surrounding area. Abstract : Microrefugia are thought to be small areas with environmental conditions enabling the survival of populations outside their species range. In this paper, we study current microrefugia inferred from plant distribution patterns, using the southernmost disconnected and abyssal populations of the circumboreal herbaceous plant Oxalis acetosella in Southern France. We show that such sites exhibit a different fine‐scale climate compared to the immediate surroundings, which goes hand in hand with floristic changes.